A comparative study of service quality in Portuguese and Angolan higher education institutions - Rolo, A.; Saraiva, M.; Leandro G.; Nogueiro, T.; Alves, R. (Driving quality management and sustainability in VUCA environments: 4th International Conference on Quality Innovation and Sustainability (ICQIS), 2024)
Quality in education is a passionate topic, which is reflected in the educational levels of a society. Many studies consider students as stakeholders, however, families, employers and society, in general, can also be considered stakeholders in this educational process. This article addresses the issue from an international perspective, that results from a collaborative work carried out by Portuguese and Angolan researchers. The aim is to study service quality in two Higher Education Institutions (HEIs), one in Portugal and one in Angola. The study was based on the HEISQUAL model, a modern approach to measuring the quality of service in higher education institutions. This survey follows a convenience sampling technique. It was possible to conclude that, for the institutions under study, the HEI located in Angola presents lower values than those obtained from the Portuguese HEI regarding the points attributed by the respondents for the evaluation of the different items, for which a 5-point Likert scale was used. Based on these results, the items that should be further worked on were identified and good practices to be implemented were identified. In addition to the scientific component, this work is based on a greater concern, namely the contribution of this study to Sustainable Development Goal (SDG) 4 – Quality Education. It is expected that the application of good practices will result in the improvement of the quality of education perceived by the students.